2022
DOI: 10.1021/acsnano.1c09108
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Nanoparticle Size to Understand Factors Affecting Hemostatic Efficacy and Maximize Survival in a Lethal Inferior Vena Cava Injury Model

Abstract: Intravenous nanoparticle hemostats offer a potentially attractive approach to promote hemostasis, in particular for inaccessible wounds such as noncompressible torso hemorrhage (NCTH). In this work, particle size was tuned over a range of <100–500 nm, and its effect on nanoparticle–platelet interactions was systematically assessed using in vitro and in vivo experiments. Smaller particles bound a larger percentage of platelets per mass of particle delivered, while larger particles resulted in higher particle ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 46 publications
3
16
0
Order By: Relevance
“…These polymers were used to generate nanoparticles (NPs) of approximately 180 nm, as previous studies had demonstrated that this size was optimal for the recruitment of activated platelets and accumulation at the injury site. [ 17 ] With the exception of pure azide NPs (only used in kinetic studies), all sizes fell within the range of 140–220 nm. The size of the nanoparticle crosslinker, also within the range of 140–220 nm, was chosen to match its biodistribution and pharmacokinetic properties to the targeting component, maximizing the timeframe over which the two components would coexist within the bloodstream.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These polymers were used to generate nanoparticles (NPs) of approximately 180 nm, as previous studies had demonstrated that this size was optimal for the recruitment of activated platelets and accumulation at the injury site. [ 17 ] With the exception of pure azide NPs (only used in kinetic studies), all sizes fell within the range of 140–220 nm. The size of the nanoparticle crosslinker, also within the range of 140–220 nm, was chosen to match its biodistribution and pharmacokinetic properties to the targeting component, maximizing the timeframe over which the two components would coexist within the bloodstream.…”
Section: Resultsmentioning
confidence: 99%
“…Characterization Methods: All synthesized materials were characterized as previously described. [17] In brief, polymers were characterized via nuclear magnetic resonance (NMR) on a Bruker Advance III DPX 400 spectrometer in deuterated DMSO at a concentration of 5 mg mL −1 . The ratio of lactide to glycolide was quantified via lactide protons (≈5.2 ppm) and glycolide protons (≈4.8 ppm), and the molecular weight of the polymer was calculated using the PEG macroinitiator as a standard (≈3.5 ppm).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations